Freedom of Will as a Prerequisite for Criminal Liability: Humans and Artificial Intelligence in a Czech Criminal Law Perspective (Ius Novum, 2026)
The paper analyses the form and place of human will in the foundations of criminal liability. It explains the necessity of will for the traditional criminal liability of natural persons and presents a comparison with the possible criminal liability of autonomous and non-autonomous systems equipped with artificial intelligence. The conclusions of the paper are negative with regard to the possible direct liability of such systems. A solution is proposed in the form of criminal liability for persons who create, control and monitor autonomous and nonautonomous systems.
Keywords: will; emotions; intuition; intelligence; artificial intelligence; algorithm; autonomous and non-autonomous systems; determinism; indeterminism; compatibilism; criminal liability; moral liability; motivation; natural person; legal person; electronic person; imputability